Evaluasi Usability Aplikasi Ibis Paint X Menggunkan Metode System Usability Scale dan User Experience Questionnaire - Asmasudirdja, Amalia Zaini; Mayatopani, Hendra (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Ibis Paint X is a drawing application that is quite in demand, because it has been downloaded by more than 100 million users with around 1.9 million reviews on the Google Play Store. Until now, there has been no research on the usability evaluation of  the  Ibis Paint X application, so there may be some unknown usability problems. This study aims to evaluate  the usability of  Ibis Paint X as a digital drawing application that is quite in demand. In evaluating the usability of Ibis Paint X, two usability measurement methods are used, namely the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The purpose of using two methods to evaluate  the usability of the Ibis Paint X application is to obtain more in-depth evaluation results from two points of view of the usability evaluation method of an application. The evaluation process was assessed by 122 respondents using the Ibis Paint X application. Based on the evaluation results of the SUS method getting a score of 68.69, judging from the interpretation of the SUS score which has 4 categories, it can be concluded that Ibis Paint X gets a "C" predicate in the grade scale category, is considered "OK" in the adjectives rating category, including "Marginal" in the category  acceptability ranges, and have users who are "Passive" in the NPS category. For the evaluation results, the UEQ method has positive results as a digital drawing application because each category of UEQ methods, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty, has an average value of more than 0.8.